Assessing the Potential of Using Artificial Intellect for Governing the Organization (illustrated by the Transportation and Logistics Holding Company) - A. A. Ulanov; A. Yu. Ulanov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article provides results of the experiment in the form of an interview with chat-bot based on artificial intellect (AI) ChatGPT dealt with governing the transportation and logistics holding company. The research showed that AI systems had reached such a level of development, which allows us to use them for solving problems of organizational and strategic governance of the company. The system can give adequate answers to questions connected with various aspects of management, formulate suggestions and identify promising trends for strategic development. Chat-bot that deals with preliminary preparation of the material can be used to resolve analytical problems in order to save time of profile specialists. However, use of such systems can cause risks of sensitive information leakage and making incorrect decisions on the basis of wrong data. In spite of high assessment of such system potential, transportation and logistics companies and other organizations should use relevant technology with care.